Radical therapy of resectable and borderline resectable pancreatic cancer – present state of knowledge. Do we have sufficient data to use neoadjuvant treatment? - Dziura, Robert; Macek, Paweł; Smok-Kalwat, Jolanta; Góźdź, Stanisław (Medical Studies/Studia Medyczne, 2020)
The incidence of pancreatic cancer has been increasing in recent years. It is expected to be the second or the third leading cause of cancer deaths in high-income countries in the next decade. Standard therapeutic management for patients with resectable pancreatic cancer is surgical resection followed by adjuvant chemotherapy. The main reason for neoadjuvant therapy is that the prognosis with current strategies is unsatisfactory, and we need new treatments to improve overall survival as well as the quality of life of the patients suffering from pancreatic cancer. The aim of this paper is to provide an overview of the recent data on the subject of neoadjuvant treatment concerning resectable and borderline resectable group of patients.